Tilted-Beam Switched Array Antenna for UAV Mounted Radar Applications with 360° Coverage - Cheol Ung Lee (Electronics, 2019)
A highly efficient antenna array for unmanned aerial vehicle (UAV) mounted radar applications with a tilted-beam characteristic and a 360° beam coverage is proposed in this paper. The proposed array antenna is configured by four planar super J-pole antennas with 2-dimensional ground reflectors. Each super J-pole antenna element provides a high directivity where the peak gain is tilted about 45° facing toward the ground from the bottom of a UAV body. Thus, the air-to-ground communication difficulty due to the altitude difference between the UAV and ground targets can be effectively solved. Further, the four super J-pole elements with a switched operation can cover the whole 360° areas around the UAV while high antenna gain is maintained. To verify the performance, the proposed structure was implemented at 5.9 GHz with an overall volume of 0.88 × 0.88 × 0.83 λo3. The measured 10-dB impedance bandwidths for all four antenna elements were better than 27.2% and the isolation among the four antenna ports was also always better than 13 dB. The measured peak gain was better than 7.4 dBi and tilted at 45° in the elevation angle. Lastly, the measured half power beam widths in elevation and azimuth planes were more than 60° and 87°, respectively.